Public Preferences for Renewable Energy Options: A Choice Experiment in Rwanda - Oluoch, Sydney; Lal, Pankaj; Susaeta, Andres; Mugabo, Rodrigue; Masozera, Michel; Aridi, Jackline (Frontiers in Climate, 2022)
Rwanda has seen impressive economic growth in the past few years due to policy driven initiatives. However, one of the key challenges to economic development in Rwanda has been the provision of reliable and cost-effective clean energy. As a result, the country has planned to expand its renewable energy portfolio to meet its energy demand and mitigate greenhouse gas (GHG) emissions. Meeting these goals requires a robust policy framework that considers the perspective of the public. Especially for women, who have been disproportionately affected by climate change. Gender equality is critical for Rwandan economic plans, as gender gaps remain a barrier to equal benefits for energy access to all. Several challenges abound in providing access to electricity and reducing the dependence on wood fuel for cooking, hence deliberate effort needs to be made to ensure gender responsiveness in energy programs and policies. This study applied a choice experiment analysis to determine how renewable energy attributes (type of energy, ownership, impact on environment, distance and visibility, community job creation and yearly renewable energy tax) impacts public willingness to pay for renewable energy development in Rwanda. A nationwide survey was conducted on 1006 households from which 58.35% were women. Analysis was conducted using the conditional logit (MNL) and random parameter logit (RPL) framework. We found out that the Rwandan public has a high utility for the following issues: environmental impact, distance and visibility, and type of renewable energy. Further analysis focusing on the gendered impacts of renewable energy use revealed that women awareness, attitude, and preferences were comparable to their male counterparts and can play a great role in developing amenable policies. From a policy standpoint, the valuable public input should be incorporated in future decision-making processes through public participation to guide policymakers in developing beneficial renewable energy programs. The momentum to participate in development of sources of renewable energy should be harnessed through development of amenable policy that involves the inclusion of public opinion.